BAYESIAN ESTIMATION OF GENERALIZED EXPONENTIAL DISTRIBUTION WITH MULTIPLE CHANGE POINTS FOR TRUNCATED AND CENSORED DATA - HE ChaoBing (Jixie qiangdu)
The complete-data likelihood function of generalized exponential distribution for truncated and censored data is obtained by filling in the missing data of the life variable using rejection method. All the parameters are sampled by MCMC method of Gibbs sampling together with random-walk Metropolis algorithm. The means of Gibbs samples are taken as the estimations of the parameters. The random simulation test results show that the estimations are fairly accurate.